Selective PPARδ Agonist GW501516 Protects Against LPS-Induced Macrophage Inflammation and Acute Liver Failure in Mice via Suppressing Inflammatory Mediators - Hyun-Joung Lim; Hyun Jeong Kwak (Molecules)
Inflammation is critical in the development of acute liver failure (ALF). Peroxisome proliferator-activated receptor delta (PPARδ) regulates anti-inflammatory responses and is protective in several diseases such as obesity and cancer. However, the beneficial effects and underlying mechanisms of PPARδ agonist GW501516 in ALF remain unclear. This study investigated the molecular mechanisms underlying the anti-inflammatory effects of GW501516 in macrophages and assessed its protective potential against lipopolysaccharide (LPS)/galactosamine (GalN)-induced ALF. In vivo administration of GW501516 significantly reduced LPS/GalN-induced hepatotoxicity, as evidenced by lower mortality, decreased liver damage, and attenuated secretion of IL-1β, IL-6, and TNF-α. GW501516 treatment also decreased LPS-induced nitric oxide synthase 2 (NOS2) expression and nitric oxide (NO) production in RAW264.7 cells, an effect reversed by PPARδ siRNA. Additionally, GW501516 inhibited LPS-induced phosphorylation of p38 and c-Jun N-terminal kinase (JNK), suggesting that inactivation of these MAPKs contributes to its effects. The secretion of IL-6, TNF-α, and NF-κB DNA-binding activity were also suppressed by GW501516, while the nuclear translocation of the NF-κB p65 subunit was unaffected. In conclusion, our findings suggest that GW501516 exerts protective effects in ALF by inhibiting the production of inflammatory mediators. Therefore, GW501516 may act as a potential agent for developing anti-inflammatory therapies for ALF.